2017
DOI: 10.1038/s41467-017-02327-0
|View full text |Cite
|
Sign up to set email alerts
|

Frustration-driven C 4 symmetric order in a naturally-heterostructured superconductor Sr2VO3FeAs

Abstract: A subtle balance between competing interactions in iron-based superconductors (FeSCs) can be tipped by additional interfacial interactions in a heterostructure, often inducing exotic phases with unprecedented properties. Particularly when the proximity-coupled layer is magnetically active, rich phase diagrams are expected in FeSCs, but this has not been explored yet. Here, using high-accuracy 75As and 51V nuclear magnetic resonance measurements, we investigate an electronic phase that emerges in the FeAs layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
29
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 47 publications
8
29
2
Order By: Relevance
“…therefore imply V ordering. Reports on 51 V and 75 As nuclear magnetic resonance (NMR) are inconsistent since they either claim Fe magnetism [40,41] or argue in favor of V magnetism [27,38]. NMR measurements on our sample (Appendix D) are in agreement with the literature data to a large extent, but they cannot provide a conclusive answer as to which element carries the ordering moments.…”
Section: μSr and Magnetization Measurementscontrasting
confidence: 50%
“…therefore imply V ordering. Reports on 51 V and 75 As nuclear magnetic resonance (NMR) are inconsistent since they either claim Fe magnetism [40,41] or argue in favor of V magnetism [27,38]. NMR measurements on our sample (Appendix D) are in agreement with the literature data to a large extent, but they cannot provide a conclusive answer as to which element carries the ordering moments.…”
Section: μSr and Magnetization Measurementscontrasting
confidence: 50%
“…S10]. We found that the C 4 order can be erased near 60 K, right above the Fe magnetic ordering temperature found in NMR measurement [29]. On the other hand, the application of a magnetic field up to 7 T does not induce any qualitative change in the C 4 (2 × 2) pattern in the Cr tip SPSTM topograph [ Fig.…”
mentioning
confidence: 54%
“…At optimal doping, the FeAs layer usually prefers C 2 magnetism harboring superconductivity, while the VO 2 layer prefers C 4 magnetism [1][2][3]21]. Previous experimental studies of Sr 2 VO 3 FeAs [22][23][24][25][26][27][28], however, have reported inconsistent results about magnetic order; recent nuclear magnetic resonance (NMR) measurements on single crystals [29] and neutron diffraction [30] experiments show that there is no long-range magnetic order in the V lattice at any temperature, while in the Fe lattice a magnetic order with a small moment of ∼0.05μ B , possibly due to frustration, is developed below 50 K. Indeed, a theoretical generalized gradient approximation (GGA) calculation has suggested that there can be a number of competing metastable magnetic states composed of different symmetries in V and Fe layers [21]. This is a reasonable theoretical prediction considering the coupling and frustration between V and Fe layers (Supplemental Material Sec.…”
mentioning
confidence: 99%
See 2 more Smart Citations